(untitled) (Scientific journal of the Fergana State University, 2026)
This study explores the role of metaphors in language and culture, showing that they are not just stylistic devices but core cognitive tools. By reviewing theories and analyzing metaphorical expressions across cultures, the research demonstrates how metaphors connect abstract and concrete domains, shape knowledge, and preserve cultural values. Findings reveal both universal cognitive patterns and culture-specific variations, highlighting metaphors as key to human thought and cultural identity.